2020
DOI: 10.1111/jam.14930
|View full text |Cite
|
Sign up to set email alerts
|

Microbially induced carbonate precipitation via methanogenesis pathway by a microbial consortium enriched from activated anaerobic sludge

Abstract: Aims Various applications of microbially induced carbonate precipitation (MICP) has been proposed. However, most studies use cultured pure strains to obtain MICP, ignoring advantages of microbial consortia. The aims of this study were to: (i) test the feasibility of a microbial consortium to produce MICP; (ii) identify functional micro‐organisms and their relationship; (iii) explain the MICP mechanism; (iv) propose a way of applying the MICP technique to soil media. Methods and Results Anaerobic sludge was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 142 publications
(134 reference statements)
0
13
0
Order By: Relevance
“…The half-life of FLO in the presence of E. adhaerens CGMCC 6315 was only 7.4 h, significantly shorter than that in FLO degradation by A. faecalis CGMCC 17553 (15 h), E. meliloti CGMCC 7333 (60 h), and Aminobacter sp. CGMCC 1.17253 (178.8 h) [ 15 , 17 , 18 ]. Therefore, E. adhaerens CGMCC 6315 may be more advantageous for microbial restoration of FLO-contaminated environments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The half-life of FLO in the presence of E. adhaerens CGMCC 6315 was only 7.4 h, significantly shorter than that in FLO degradation by A. faecalis CGMCC 17553 (15 h), E. meliloti CGMCC 7333 (60 h), and Aminobacter sp. CGMCC 1.17253 (178.8 h) [ 15 , 17 , 18 ]. Therefore, E. adhaerens CGMCC 6315 may be more advantageous for microbial restoration of FLO-contaminated environments.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis based on the amino acid sequences of NHase α -subunits indicated that CnhA clustered in a branch with the NHase of other FLO degrading bacteria, E. meliloti CGMCC 7333 and Aminobacter sp . CGMCC 1.17253 [ 17 , 33 ], with 82.33 and 74.42% protein sequence similarity respectively. Comparing E. adhaerens CGMCC 6315 PnhA and CnhA with the enzymes from E. meliloti CGMCC 7333, the protein similarities were 51.63% and 82.33%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Engineering responses to biotreated soil are reported to be affected by many factors : (1) environmental, which includes rainwater flushing (Mortensen et al 2011;Tang et al 2020), contamination (Cheng and Shahin 2017;Yu and Jiang 2020), temperature (Ferris et al 2004;Nemati et al 2005;Sun et al 2019b), acid rain (Gowthaman et al 2021), oxygen content (Li et al 2017a;Su and Yang 2021), salinity (Mortensen et al 2011;Tang et al 2020), wetting-drying cycles (Sharma and Satyam 2021), and freezethaw cycles (Sharma et al 2021a;Sun et al 2021b); (2) treatment and testing factors, which include chemical concentrations (Al Qabany et al 2012;Zhao et al 2014), flow rate and direction of chemical media (Martinez et al 2013), calcium resource (Choi et al 2016b;Wang et al 2021b), treatment strategy (Al Qabany et al 2012;Martinez et al 2013;Cheng and Shahin 2016), urease source (e.g., indigenous or exogenous microbes) (Dhami et al 2013b;Park et al 2014;Cheng et al 2017a;Bibi et al 2018;Gomez et al 2018b;Nayanthara et al 2019;Marin et al 2021), bacterial concentration (Bosak et al 2004;Soon et al 2014), pH (Wu et al 2019a;Zehner et al 2020), and curing time for the soaking method (Zhao et al 2014;Sharma and Satyam 2021); (3) characteristics of base materials, which include particle mineralogy…”
Section: Introductionmentioning
confidence: 99%